TINJAUAN YURIDIS PENGGUNAAN SURAT BERHARGA DALAM OPERASIONAL PERBANKAN - Ahyani Yunus (Maleo Law Journal, 2020)
The use of Securities in banking operations is a necessity. This was mainly motivated by the fact that banking business activities engaged in the financial industry require instruments to link customer rights and obligations without any movement of cash. Basically, Securities that enter the traffic of banking business activities are Securities related to the payment system. This means that it is needed by the community to support business activities or community needs in the payment system. In contrast to Capital Market Securities such as shares and bonds or the like, issued in the context of raising funds for business development purposes. Thus, the traffic of activities related to Capital Market Securities is related to investor interest in investing and obtaining profitability. Securities act as a medium for transferring a creditor's collection rights to another party and as a payment instrument. The transfer of rights can be carried out sequentially from one party to another, until the maturity period. This process simultaneously shows that Securities are functioning as means of payment, transfer of collection rights as well as proof of receivables. Securities play a role in carrying out the function of money in various financial activities, especially those related to the payment system. Keywords: Operational Banking. Securities